Analisis Grafik Deflectometry Dalam Perencanaan Tebal Lapis Tambah ( Overlay ) ( Studi Kasus : Jalan Kubang Raya Pekanbaru ) - M Andy Kurniawan Lubis; Muhammad Yusa; Elianora Elianora (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Kubang Raya Road section is a district road linking between panam pekanbaru with left Kampar, this road has 2 lanes, length 17 km, and witdth 6 m. visually there has been road demage such as ctacked roads and potholes. The prolonged destruction of road infrastructure will result in cracks of the damage it self, in other words a damaged road if not repaired then the damage will get worse. For that matter need handling of road damage optimally. To overcome this can be done by giving layer added. The goal is to calculate the added layer by the pd T-05-2005-B Method based on the deflection obtained by using the Benkelman beam tool. Also analyze the couses of deflection that occur using image deflectometry. From this research, it is found that the layers are divided. Into 3 alternatives, each of which consists of several segments as an alternative of 1 segment of read of 26 cm, alternative 2 consists of 2 segments of 19 cm and 32 cm, while alternative 3 consists of 4 segments of 20, 24, 26 and 25 cm. As for its deflectometry analysis, the stations with poor pavement conditions are Sta 01+200 until sta 02+400 and sta 03+000.Keywords: Layer added, Pd T-05-2005-B, Deflectometry, Benkelman beam